2021
DOI: 10.1038/s41598-021-95028-0
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223 inhibits neutrophil extracellular traps formation through regulating calcium influx and small extracellular vesicles transmission

Abstract: Modulation of miRNAs and neutrophil extracellular traps (NETs) formation are both implicated in inflammatory disorders. Adult-onset Still’s disease (AOSD) is a systemic autoinflammatory disease with neutrophilic leukocytosis and unknown etiology. Although the NETs formation is elevated in AOSD patients, the regulatory roles of miRNAs in NETs formation in AOSD remains unclear. We revealed that the circulating levels of IL-18, NETs, and miR-223 were significantly higher in active AOSD patients, compared with ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Another molecule involved in this process is microRNA–223, which modulates the immune response of the host. In this study, a fine-tuned mechanism was proposed in which IL–18, microRNA–223, and NET formation regulate inflammation in AOSD, in which NET formation inhibits calcium influx into neutrophils by upregulation of microRNA–223, and it eventually inhibits IL–18 mediated NET formation [ 110 ]. The role of LDGs and NET formation in AOSD was also identified, and it has been reported that the concentration of high mobility group box–1 protein (HMGB–1) and cathelicidin LL–37 in NETs was increased in patients with AOSD [ 111 ].…”
Section: Nets In Sjia and Aosdmentioning
confidence: 99%
“…Another molecule involved in this process is microRNA–223, which modulates the immune response of the host. In this study, a fine-tuned mechanism was proposed in which IL–18, microRNA–223, and NET formation regulate inflammation in AOSD, in which NET formation inhibits calcium influx into neutrophils by upregulation of microRNA–223, and it eventually inhibits IL–18 mediated NET formation [ 110 ]. The role of LDGs and NET formation in AOSD was also identified, and it has been reported that the concentration of high mobility group box–1 protein (HMGB–1) and cathelicidin LL–37 in NETs was increased in patients with AOSD [ 111 ].…”
Section: Nets In Sjia and Aosdmentioning
confidence: 99%
“…Serum CXCL10, CXCL13 ( 54 ) and S100A12 ( 55 ) levels can be used as clinical markers to assess the disease activity of AOSD. Chen, D.Y’s team found that there is a fine-tuned mechanism between inflammatory and anti-inflammatory factors in AOSD ( 56 ), and IL-18 is an important predictor of active AOSD ( 57 ). In addition, galectin-3 ( 58 ), C-Type Lectin Domain Family 5-Member A ( 59 ), B19-NS1 ( 60 ), microRNA-134 ( 61 ), and the NLRP3 inflammasome ( 62 ) are involved in the pathogenesis of AOSD.…”
Section: Discussionmentioning
confidence: 99%
“…S100 A8/A9 and A12 are parts of NETs, function as DAMPs, and act as the ligand of TLR4 or RAGE, involved in the pathogenesis of AOSD by enhancing the feedback loop (36,48,49). IL-18 is widely reported to be increased in the serum of AOSD patients, and an updated study found that it regulates mitochondrial ROS generation by increasing calcium influx to induce the formation of NETs in a process which could be suppressed by microRNA-223 (50). Hu and colleagues reported a gene of leukocyte immunoglobulin-like receptor (LIR)-A3 (LILRA3) that plays a pathogenic role in AOSD and speculated that the functional LILRA3 is a new genetic susceptibility factor for neutrophil activation and NETosis in AOSD (51) conducted a study that revealed increased type I interferon (IFN) could induce NETs, especially ones containing oxidized mitochondrial DNA in AOSD (46).…”
Section: Innate Immune Systemmentioning
confidence: 99%